2016
DOI: 10.1186/s13104-016-2155-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of women in family planning and future desire to use contraception: a cross sectional survey in Urban Cameroon

Abstract: BackgroundThe rate of modern contraceptive use will be on an increase and maternal mortality on a decrease if women had a good knowledge on family planning and its methods. This survey was designed to evaluate the knowledge and determine the future desires to use contraception among women in Urban Cameroon.MethodsWe conducted a cross sectional community based survey from March 2015 to April 2015 targeting women of childbearing age in the Biyem-Assi Health District. Participants were included using a multistep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 8 publications
2
28
0
1
Order By: Relevance
“…In Côte d'Ivoire, 15% of these deaths are related to unsafe abortions (Guillaume and Loû, 2002). The good knowledge on family planning and its methods will reduce the rate of mortality of women (Ajong et al, 2016). Indeed, unsafe abortion is one of the main causes of women death.…”
Section: Introductionmentioning
confidence: 99%
“…In Côte d'Ivoire, 15% of these deaths are related to unsafe abortions (Guillaume and Loû, 2002). The good knowledge on family planning and its methods will reduce the rate of mortality of women (Ajong et al, 2016). Indeed, unsafe abortion is one of the main causes of women death.…”
Section: Introductionmentioning
confidence: 99%
“…Women who had primary and above educational attainment have consistently increased in the use of modern contraceptives in the last fifteen years. Similarly, studies showed that females' education of primary and above educational status have highly significant effects to increase contraceptive prevalence (27,(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…The family planning (KB) program has an essential role in creating a welfare and quality of health care for family in Indonesia. The contraception service aims to fulfill the needs of society in creating and implementing the quality family planning needs, to avoid unwanted pregnancy, thus it can make the society satisfy (Profil Kesehatan Republik Indonesia, 2015; Heike Theil de Bocanegra et al, 2016;Smith et al, 2013;Ajong Njotang et al, 2016;Rafidah, 2012).…”
Section: Introductionmentioning
confidence: 99%